I am Queen Mary: On sustained protest and Denmark's 'colonial amnesia'. (19th May 2022) - Grøn, Helene
Abstract : This article focuses on sustained protest through the I am Queen Mary statue, sitting in front of the West Indian Warehouse in Copenhagen's waterfront. I am Queen Mary was co-created by artists La Vaughn Belle and Jeannette Ehlers, and inspired by Mary Thomas, a key figure of rebellion from the 1878 Fireburn labour revolt on St Croix against the 'contractual servitude that continued to bind workers to the plantation system after the 1848 abolition of slavery' (Ehlers and Belle n.d.). The statue is then 'a hybrid of bodies, nations and narratives' (Ehlers and Belle n.d.) that simultaneously invites the viewer into reflections on Denmark's 'colonial amnesia' (Belle n.d., 2019; Ehlers and Belle n.d.; Stenum 2017; Odumosu 2019). Through the lens of Laura Shalson and Mary Lynne Gasaway Hill's thinking on performance and protest, the following analyses I am Queen Mary from her artistic making, to the invitation into critical and reflective viewership and the necessary ongoing campaigning for a 'permanent space to holistically tell the history of slavery and colonialism' (Odumosu, 2019: 628).